2003
DOI: 10.1016/s0741-5214(03)00129-0
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation is increased in peripheral arterial disease

Abstract: Platelet activation is increased in patients with peripheral arterial disease, suggesting an underlying prothrombotic state. Platelets from patients with critical limb ischemia are less responsive to in vitro stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 21 publications
7
65
1
2
Order By: Relevance
“…Furthermore activated leukocytes release thromboxane A2, which in addition to be a vasoconstrictor, promotes platelet aggregation [27], so inducing the phenomenon of platelet plugging. To this phenomenon in claudicants may also participate overexpression of P-selectin [28,29] which mediates platelet-endothelium interaction [30]. Consistent with the observation by Neumann et al [26], our group observed that in the claudicant limb, but not in the healthy legs of the control group, maximal exercise increased the transfemoral venous-arterial difference of the neutrophil myeloperoxidase (MPOx) content [31], an index of neutrophil activation and a well established marker of inflammation [32].…”
Section: Effect Of Ischemia On Endotheliumsupporting
confidence: 86%
“…Furthermore activated leukocytes release thromboxane A2, which in addition to be a vasoconstrictor, promotes platelet aggregation [27], so inducing the phenomenon of platelet plugging. To this phenomenon in claudicants may also participate overexpression of P-selectin [28,29] which mediates platelet-endothelium interaction [30]. Consistent with the observation by Neumann et al [26], our group observed that in the claudicant limb, but not in the healthy legs of the control group, maximal exercise increased the transfemoral venous-arterial difference of the neutrophil myeloperoxidase (MPOx) content [31], an index of neutrophil activation and a well established marker of inflammation [32].…”
Section: Effect Of Ischemia On Endotheliumsupporting
confidence: 86%
“…Preserving ambulation in PAD patients leads to favorable effects on prognostic factors for lethal coronary artery disease and cerebrovascular disease, 20 just as the existence of PAD suggests ongoing thrombogenesis in other tissues. 21,22 Therefore, alleviating PAD not only diminishes the risk of limb loss, but may also reduce patient mortality from atherothrombosis in other vascular beds.…”
Section: Discussionmentioning
confidence: 99%
“…The common 1565T→C polymorphism in exon 2 of the GPIIIa gene is associated with increased platelet aggregability and myocardial infarction (Weiss et al 1996). This Leu33Pro amino acid substitution (PI A2 or HPA-1b) results in a conformational change in the amino-terminal disulfide loop involved in fibrinogen binding (Honda et al 1995) and highlights the important role of increased platelet activation in the development of vascular disease (Cassar et al 2003;Cherian et al 2003).…”
Section: Introductionmentioning
confidence: 99%